Innovations in anesthesia: Advances and ethical considerations (Research, Society and Development, 2024)
Understanding how these innovations are shaping the practice of anesthesiology and how emerging ethical issues are being addressed is critical to ensuring that patients receive the highest standards of care and that healthcare professionals are prepared to deal with the contemporary challenges they face. This research aims to contribute to the development of guidelines and policies that promote ethical and safe practices in anesthesiology, while driving innovation and progress in the field. A systematic review of the literature was carried out, through a survey of data in scientific databases: LILACS, PUBMED, SCIELO, VHL and Web of Science. The introduction of new techniques, such as ultrasonic guided regional anesthesia, has demonstrated significant benefits in reducing postoperative pain and improving patients' functional recovery. Additionally, advances in anesthetic medications, such as short-acting volatile anesthetic agents and alternative opioids, are providing safer and more effective therapeutic options. These innovations are redefining standards of anesthesia care, enabling more individualized and less invasive approaches. However, it is crucial to examine the ethical implications of these innovations in clinical practice. A central ethical consideration is the need to ensure patients' informed consent to new techniques and therapeutic options available.